The Accountability of Nonprofit Hospitals: Lessons from Maryland's Community Benefit Reporting Requirements - Bradford H. Gray; Mark Schlesinger (SAGE Publishing, 2009)
Under Internal Revenue Service requirements, nonprofit hospitals will begin filing new community benefit reports in 2010. Maryland has had similar requirements since 2004. This paper, based on interviews at 20 hospitals, describes how Maryland's requirements affected hospitals and their activities. Increases in reported community benefit expenditures since the program began are due to both changes in activities and better data capture. Charity care accounts for one-third of community benefit dollars. A key distinction concerns whether hospitals take an accounting or managerial approach to community benefit. The Maryland experience suggests the issues that will arise when the national requirements are implemented.